Green chemistry in industry - Benvenuto, Mark A.; Plaumann, Heinz (Green chemical processing, 2018)
The "greening" of industry processes, i.e. making them more sustainable, is a popular and often lucrative trend which has emerged over recent years. The 3rd volume of Green Chemical Processing considers sustainable chemistry in the context of corporate interests. The American Chemical Society's 12 Principles of Green Chemistry are woven throughout this text as well as the series to which this book belongs.